Developing Mobile Web ArcGIS Applications - Sheehan, Matthew (EBL-Schweitzer, 2015)
Cover; Copyright; Credits; About the Author; About the Reviewers; www.PacktPub.com; Table of Contents; Preface; Chapter 1: Introduction to Mobile Web ArcGIS Development; Screen size; Interacting with mobile applications; From clickable to tappable; New data input and collection methods; Providing interaction feedback; Designing for mobile; Simplicity and intuition; Layout; Orientation; Styling; Mobile Targeted functionality; Focused mobile applications; Target audience GIS versus non-GIS users; Fast responding mobile applications; Working with mobile browsers